2018
DOI: 10.1007/978-3-319-70007-6_9
|View full text |Cite
|
Sign up to set email alerts
|

Does Diversity of Bank Board Members Affect Performance and Risk? Evidence from an Emerging Market

Abstract: This study investigates the influence of background diversity of bank board members on performance and risk. Using data from Indonesian banks from 2001 to 2011 covering 4200 individual year observations and 21 ethnic groups, we estimate the degree of diversity by considering various aspects (gender, citizenship, age, experience, tenure, ethnicity, nationality, education level and type) and find significant impacts on bank performance. On the whole, diversity is in general positively associated with performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 110 publications
3
19
0
Order By: Relevance
“…It is found also significant positive with credit risk at the level 0.05, while it is negative significant with liquidity risk at the 0.10 level, accordingly, more female members will decrease both insolvency risk, liquidity risk and increase credit risk, therefore hypothesis 4 is partially accepted. The findings are consistent with the results of [11,47] who find a negative relation between gender diversity and risk-taking predicting that board females are risk averse. One explanation of having a positive correlation with credit risk is that the presence of women on boards doesn't hinder them from providing loans to their customers as loans is the core of bank business, beside the poor percentage of women existence in the board (on average 6.50%).…”
Section: Results Of Correlation and Regression Analysissupporting
confidence: 90%
See 2 more Smart Citations
“…It is found also significant positive with credit risk at the level 0.05, while it is negative significant with liquidity risk at the 0.10 level, accordingly, more female members will decrease both insolvency risk, liquidity risk and increase credit risk, therefore hypothesis 4 is partially accepted. The findings are consistent with the results of [11,47] who find a negative relation between gender diversity and risk-taking predicting that board females are risk averse. One explanation of having a positive correlation with credit risk is that the presence of women on boards doesn't hinder them from providing loans to their customers as loans is the core of bank business, beside the poor percentage of women existence in the board (on average 6.50%).…”
Section: Results Of Correlation and Regression Analysissupporting
confidence: 90%
“…It is also found a positive significant relation with credit risk, while it is negative significant with liquidity risk, accordingly, more female members will decrease both insolvency risk, liquidity risk and increase credit risk. The findings are consistent with the studies that found a negative relation between gender diversity and risk-taking predicting that board females are risk averse [11,47]. Board members with a PhD degree has positive insignificant relation with the three measures of risks which is a contrast to the finding of [9], who find that better educated board members decrease portfolio risk, and with [20], who found higher education increase the bank risk-taking.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Due to the conservative nature of woman, woman director can correct bias in important decisions especially those related to strategic oversight and risk by thinking about problems and detailing solutions, so woman is often considered more conservative than men [31] [32]. Bellucci et al [33] and Beck et al [34] focus on the implications of gender differences in the banking context. Bellucci et al [33] found that woman credit employee avoid risk more than male credit employees and limit the availability of credit to new borrowers.…”
Section: Woman Director and Riskmentioning
confidence: 99%
“…Bellucci et al [33] found that woman credit employee avoid risk more than male credit employees and limit the availability of credit to new borrowers. Beck et al [34] shows that loans handled by woman credit employee have significantly reduced the failure rate.…”
Section: Woman Director and Riskmentioning
confidence: 99%